2019
DOI: 10.1590/1807-2577.02119
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between dentition, anthropometric measurements, and metabolic syndrome in the elderly

Abstract: Introduction Tooth loss is a health disorder of the elderly population that may lead to masticatory deficiency and nutritional risks, inducing the biochemical changes of metabolic syndrome (MS). Objective To verify the relationship among number of teeth, anthropometric measurements, and MS in a group of elderly people. Material and method The study was developed in Porto Alegre, RS, Brazil, and it was divided into three phases. The first phase collected information from the database of all project participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(32 reference statements)
1
1
0
Order By: Relevance
“…50-64 aged group compared to 65 and older group was more in being risk of metabolic syndrome of this study and this result was supported by another study (Pedro et al, 2019). In the point of view of periodontitis, as a key indicator of oral health, which was identi ied as the strong in luencing factor of metabolic syndrome of this study, was partially in consistent with the result of another study even though there are difference in the aspects of racial sample and study design (Uloma et al, 2019) and it was supported by another study which was reported on association between oral health and metabolic syndrome among elderly (Pedro et al, 2019) even though the difference in gender. And that, even the awareness and habits of oral care was reported to be contributed to improving of life satisfaction as well as lifestyles of the elderly (Hirano et al, 2019).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…50-64 aged group compared to 65 and older group was more in being risk of metabolic syndrome of this study and this result was supported by another study (Pedro et al, 2019). In the point of view of periodontitis, as a key indicator of oral health, which was identi ied as the strong in luencing factor of metabolic syndrome of this study, was partially in consistent with the result of another study even though there are difference in the aspects of racial sample and study design (Uloma et al, 2019) and it was supported by another study which was reported on association between oral health and metabolic syndrome among elderly (Pedro et al, 2019) even though the difference in gender. And that, even the awareness and habits of oral care was reported to be contributed to improving of life satisfaction as well as lifestyles of the elderly (Hirano et al, 2019).…”
Section: Resultssupporting
confidence: 89%
“…And more, oral health was reported to be closely connected with improving of overall health especially among adults (Uloma et al, 2019;Ismail et al, 2019;Rawal et al, 2019). In addition to that number of teeth, as the important indicator of oral health, was reported to increase the risk of metabolic syndrome among elderly (Pedro et al, 2019). Additionally, diabetes and smoking were closely associated with poor oral health such as tooth loss by recent cohort study (Kim et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%